Manganese Ore Minerals Assemblages and Mineral Paragenesis with the Help of Ore Petrography and XRD Studies of Balaghat District, (M.P.) India. (Global Journal of Science Frontier Research, 2015)
The regionally metamorphosed syngenetic sedimentary bodies of manganese ores in the Sausar Group of Balaghat district, Madhya Pradesh exhibit a definite trend in the formation and transformation of manganese oxide phases with progressive metamorphism. A regional trend is clearly noticeable from the paragenesis of Ore minerals in the manganese ore bodies from different metamorphic zones. Braunite forms at a very low temperature, appearing in the chlorite zone of regional metamorphism, and it continues in stable form right up to the sillimanite zone. Bixbyite as a high temperature mineral appears first in biotite zone and also appears in the sillimanite and almandine zone in the Balaghat. It shows evidences, at places, of conversion to hausmannite, and a second generation of this mineral is also found to have been formed as conversion product in the cleavages of the latter in ore bodies of sillimanite zone in Tirodi areas. Free hausmannite is characteristic of only the sillimanite zone. Bixbyite is accompanied by hollandite which is also a transformation product of psilomelane formed in elevated temperature condition. The association of braunite, bixbyite and hollandite (in the absence of jacobsite, hausmannite and vredenburgite) continues to the almandine zone (Bharweli-Ukwa area).
Keywords: manganese ore; sausar group; balaghat district; metamorphism; paragenesis; metamorphic zones; manganese oxide minerals